Indirect land use change (iLUC) revisited: An evaluation of current policy proposals - Ruth Delzeit; Gernot Klepper; Mareike Söder (Kiel Institute for the World Economy (IfW), 2017)
The contribution of biofuels to save greenhouse gas emissions has been challenged over the last years. A still unresolved question is how to quantify emissions from indirect land use change (iLUC). In this article we discuss the implications of uncertainties on the current policy proposals in the European Union (EU). We conclude that it is inappropriate to calculate crop-specific iLUC-emissions and to include them into binding regulation. We argue that modelling results, particularly crop-specific ones, should not be used for policy decisions. Our discussion of the current EU policy proposal suggests that a combination of an increase in the minimum emissions savings threshold and limits to biofuel production are a safe way to ensure with a high degree of certainty a climate mitigation impact of biofuels.
Keywords: Q42; Q24; Q48; Q16; 330; biofuel policy; indirect land use change; European Union; policy proposals